Sound Formations: Towards a Sociological Thinking-with Sounds - Bocquillon, Rémy (transcript, 2022)
Is it possible to work with sound in sociology rather than being about sound? Can there be a »sonic sociology«? Rémy Bocquillon reflects on the process-oriented character of sociology as an experimental science by including aesthetic practices of sounding and listening as constitutive for the making of sociological theory. Following new materialist and speculative philosophies, this study is thus a combination of sociological theory, philosophical thought and aesthetic practices, not understood as discrete fields of inquiry, but co-constituting each other. It also features an audio chapter, »feeding-back« the sonic experimentations at the core of the research in new and engaging ways.